A Robust Sensorless Control of PMSM Based on Sliding Mode Observer and Model Reference Adaptive System - Larbi M’hamed; Gherabi Zakaria; Doudar Khireddine (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
This paper is intended to study and compare the operation of two methods for estimating the position/ speed of the permanent magnet synchronous motor (PMSM) under sliding mode control. The first method is a model reference adaptive system (MRAS). The second method based on sliding mode observer (SMO). The stability condition of Sliding Mode Observer was verified using the Lyapunov method to make sure that the observer is stable in converging to the sliding mode plane. In this paper the performances of the proposed two algorithms are analyzed using SIMULINK/MATLAB. The simulations results are presented to verify the proposed sensorless control algorithms and can resolve the problem of load disturbance effects by simulations which verify that the two closed-loop control system is robust with respect to torque disturbance rejection.